Simulation of the Decomposition of Natural Gas Hydrate in Porous Media by Hot Water Injection - Zhou, Xitang; Tao, Xianhua; Liang, Deqing; Fan, Shuanshi (2008)
As a reference of the recovery of natural gas hydrates by hot water injection, the decomposition of natural gas hydrates in sediments due to heat stimulation was simulated experimentally and numerically. It is supposed the radial diffusion model describes the decomposition of natural gas hydrates in sediments owing to hot water injection, and the hydrate decomposition is a one-order reaction. Combining the rate equation of the decomposing reaction with the rate equation of the heat transfer and heat balance equation, the relationship between the accumulative quantity of methane and decomposing time t was obtained i.e. n(o) - n(H) = 2.7 x 10(-2) (theta(3) - 10)(1/2)t(3/2). By comparing the results from the experiment and numerical simulation, it was found that, under the experimental conditions, the rate coefficient of hydrate decomposition was 2.675x10(-4) mol/(m(2)-Pa.min), which was found to be consistent with the experimental results.